Cryptochrome 1a localisation in light- and dark-adapted retinae of several migratory and non-migratory bird species: no signs of light-dependent activation. Issue 3 (4th May 2021) - Bolte, Petra; Einwich, Angelika; Seth, Pranav K.; Chetverikova, Raisa; Heyers, Dominik; Wojahn, Irina; Janssen-Bienhold, Ulrike; Feederle, Regina; Hore, Peter; Dedek, Karin; Mouritsen, Henrik
Abstract : The magnetic compass of birds seems to be based on light-dependent radical-pair processes in the eyes. Cryptochromes are currently the only candidate proteins known in vertebrates that may serve as the primary radical-pair-based magnetoreceptor molecules. Previous immunohistochemical studies have suggested that cryptochrome 1a (Cry1a) is localised in the photoreceptor outer segments of the ultraviolet/violet (UV/V) cones, and it has been claimed that differences in Cry1a antibody staining intensities show that Cry1a is activated by light and that this should make Cry1a the most likely magnetoreceptive candidate molecule. Here, we present an independent study of Cry1a distribution within retinae of several bird species, ranging from non-migratory domestic chicken and rock pigeon to night-migratory passerines, using both the previously used antibody and two newly generated antibodies, one against the same epitope as the originally used antibody and one against a different epitope of Cry1a. We confirm the UV/V cone outer segment localisation of Cry1a in all the tested bird species. In some stainings, we found Cry1a immunoreactivity as a distinct punctate pattern throughout the whole length of the UV/V cone outer segments. These dots with a diameter of around 170 nm might suggest that many Cry1a molecules accumulate in distinct spots in the UV/V cone outer segments. However, we did not see any notable difference in Cry1a immunoreactivity between light- and dark-adapted retinae. We find no evidence whatsoever that a C-terminal antibody against Cry1a labels only a light-activated form of the Cry1a protein.